DNA barcoding and morphology support the division of Elachista nuraghella sensu auctorum (Lepidoptera: Elachistidae: Elachistinae) into two vicariant species - Kaila, Lauri; Mutanen, Marko (Zootaxa, 2012)
Elachista nuraghella sensu auct. (Lepidoptera, Elachistidae) is shown to display a striking division of haplotype groups in theDNA barcode sequence, one widely distributed in the western Mediterranean region, the other in the east: Bulgaria, Greece andTurkey. The haplotypes correspond with constant differences in both male and female genitalia, and generally also in outerappearance. E. nuraghella Amsel is thus considered to consist of two species displaying a vicariant distribution pattern. The eastern taxon is described as Elachista grotenfelti Kaila sp. nov.